Regorafenib Plus FOLFIRI With Irinotecan Dose Escalated According to Uridine Diphosphate Glucuronosyltransferase 1A1 Genotyping in Patients With Metastatic Colorectal Cancer - Ma, Cheng-Jen (Oncol Res, 2017)
We analyzed the results of previously treated patients with metastatic colorectal cancer (mCRC) who received regorafenib plus FOLFIRI with the irinotecan dose escalation on the basis of uridine diphosphate glucuronosyltransferase 1A1 (UGT1A1) genotyping. Thirteen patients with previously treated mCRC were subjected to UGT1A1 genotyping between October 2013 and June 2015 and were administered regorafenib plus FOLFIRI with irinotecan dose escalation. Patients with UGT1A1*1/*1 and *1/*28 genotypes were administered 180 mg/m(2) of irinotecan, whereas those with the UGT1A1*28/*28 genotype were administered 120 mg/m(2) of irinotecan. For all patients, the irinotecan dose was increased by 30 mg/m(2) every two cycles until grade ≥3 adverse events or severe adverse events developed, following which the dose was reverted to and maintained at the previously tolerated level. The oral regorafenib dose was adjusted to 120 mg/day daily. The median follow-up period was 10.0 months (1.0–21.0 months). The disease control rate was 69.2%, whereas the median progression-free survival and overall survival were 9.5 and 13.0 months, respectively. Our findings indicate that regorafenib plus FOLFIRI with irinotecan dose escalation based on UGT1A1 genotyping in previously treated patients with mCRC and with UGT1A1*1/*1 and UGT1A1*1/*28 genotypes is clinically effective and yields improved oncological outcomes.